Star guard - Norton, Andre (New York : Harcourt, Brace & World, 1955)
In 3956 A.D. the inhabitants of the planet Terra struggle to keep themselves from being annihilated
Keywords: Science fiction; Science fiction, American; Science fiction Juvenile